The Use of the Image Streaming Method on the Ability to Write Short Stories in Grade V at SD Negeri 15 Marapi - Monica Wahyu Pertiwi; Siti Fatimahtun Zahra; Siti Muflihah; Hawa Hasan; Syamsul Darmawan; Irma Suriani; Deni Yuliani; Aristanto Aristanto; Ma`rifatul Jannah; Mawaddah Mawaddah (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
Learning short stories in elementary schools is one of the learning materials in the Indonesian language subject. This study aims to determine how the image streaming method is used in short story writing. This study used a qualitative method. The subjects were fifth-grade students at SD Negeri 15 Maripi. Data collection techniques used in this study included tests, interviews, and documentation. The research instrument used was a test. Documentation includes records of past events. In this study, documentation was in the form of photographs taken during the research process. Data analysis techniques were carried out using an interactive analysis model consisting of four components: data collection, data reduction, data presentation, and conclusion drawing. This research data was validated using content validity, source triangulation, and triangulation of data collection techniques. Based on the collected data, fifth-grade students at SD Negeri 15 Maripi showed an increase in short story writing skills implemented in the pre-action cycle, which showed an increase in the average score and the percentage of classical completion of students' short story writing skills. Thus, it can be concluded that short story writing skills in Indonesian language subjects improved with the use of the Image Streaming method.